Demonstrating Principle Aspects of Peptide‐ and Protein‐ Based Hydrogels Using Metallogels Examples. Issue 9 (14th July 2022) - Ghrayeb, Mnar; Chai, Liraz
Abstract: Hydrogels are 3‐dimensional networks composed of synthetic or natural polymers that absorb and retain water. They are formed when polymeric chains are cross‐linked by covalent or non‐covalent bonds. Hydrogels formed by peptides and proteins are unique due to their bioactivity and biocompatibility. Particularly interesting peptide‐ or protein‐based hydrogels are metallogels, hydrogels that form by proteins and peptides that interact with metal ions. Metallogels are potential candidates for medical applications because metal ions are essential for living organisms, for example in respiration, proper growth and development of tissues, red blood cell formation, and immune system stimulation. In this review, we describe general principles of hydrogel formation and we demonstrate them using specific metallogels examples. We focus on physically cross‐linked hydrogels and briefly review their formation mechanism, characterization, mechanical properties, and applications. Abstract :